Evaluation of Slope Stability in Mining Areas Using the Morgenstern Price Method - Haeriska, Haeriska; Chaerul, Muhammad; Desi, Natsar; Harun, A. Muh. Yusuf; Erniati, Erniati; Marzuki, Ismail (Newinera Publisher, 2025)
Indonesia’s mining sector, particularly in areas like Morowali Regency, Central Sulawesi, faces significant geotechnical challenges due to its location in the Pacific Ring of Fire. One of the key concerns in open-pit mining operations is slope instability, which can lead to landslides, threaten worker safety, damage infrastructure, and disrupt production. This study evaluates the slope stability in the Sambalagi site of PT. Wosindo Berkat Abadi using the Morgenstern-Price method, a limit equilibrium approach known for its accuracy in heterogeneous slope conditions. Field data were collected, including slope geometry, geological conditions, material strength, and hydrogeological factors. The safety factor (FK) was calculated based on geotechnical parameters such as cohesion, internal friction angle, and unit weight of the slope materials primarily saprolite and limonite. The actual slope FK value at PIT D was found to be 0.974, below the standard requirement (≥1.3) set by the Ministerial Decree No. 1827K/30/MEM/2018. To improve stability, a revised slope design was proposed, including reducing slope angles to 35°, increasing bench widths to 2 meters, and decreasing slope height per bench to 4 meters. The simulation of this revised geometry showed that it could achieve the required FK value. The study contributes to safer and more efficient mine planning by demonstrating the importance of integrating detailed geotechnical analysis in slope design, especially in tropical high-rainfall mining regions.